Poly(ADP-ribose)polymerases inhibitors prevent early mitochondrial fragmentation and hepatocyte cell death induced by H(2)O(2) - Martín-Guerrero, Sandra M. (PLoS One, 2017)
Poly(ADP-ribose)polymerases (PARPs) are a family of NAD(+) consuming enzymes that play a crucial role in many cellular processes, most clearly in maintaining genome integrity. Here, we present an extensive analysis of the alteration of mitochondrial morphology and the relationship to PARPs activity after oxidative stress using an in vitro model of human hepatic cells. The following outcomes were observed: reactive oxygen species (ROS) induced by oxidative treatment quickly stimulated PARPs activation, promoted changes in mitochondrial morphology associated with early mitochondrial fragmentation and energy dysfunction and finally triggered apoptotic cell death. Pharmacological treatment with specific PARP-1 (the major NAD(+) consuming poly(ADP-ribose)polymerases) and PARP-1/PARP-2 inhibitors after the oxidant insult recovered normal mitochondrial morphology and, hence, increased the viability of human hepatic cells. As the PARP-1 and PARP-1/PARP-2 inhibitors achieved similar outcomes, we conclude that most of the PARPs effects were due to PARP-1 activation. NAD(+) supplementation had similar effects to those of the PARPs inhibitors. Therefore, PARPs activation and the subsequent NAD(+) depletion are crucial events in decreased cell survival (and increased apoptosis) in hepatic cells subjected to oxidative stress. These results suggest that the alterations in mitochondrial morphology and function seem to be related to NAD(+) depletion, and show for the first time that PARPs inhibition abrogates mitochondrial fragmentation. In conclusion, the inhibition of PARPs may be a valuable therapeutic approach for treating liver diseases, by reducing the cell death associated with oxidative stress.